Spontaneous Rupture of Spleen in Pregnancy: Three Different Case Reports - Islam, Sardar Rezaul; Biswas, Bonika; Noor, Tania (British Journal of Healthcare and Medical Research, 2025)
We are reporting 3 cases of spontaneous rupture of spleen in pregnancy with different presentation. The first patient was a 25 years old primigravida with twine pregnancy. She was admitted with fetal and maternal distress at 34 weeks of gestation. During C-section hemoperitoneum and persistent hemorrhage was noted in the peritoneal cavity. On surgical consultation exploratory laparotomy was done. Splenic rupture was detected and splenectomy was performed. The second patient was a 32 years old woman with twine pregnancy in her 2nd gravida presented at 33 weeks of pregnancy with fetal distress and had undergone C-section. She developed intraperitoneal hemorrhage within 6 hours after C-section. Relaparotomy discovered rupture of spleen and again splenectomy was done. Her rupture spleen was missed during C-section. All these two patients required admission in intensive care unit (ICU) post operatively and received multiple transfusions. They recovered fully with their live babies. Third patient was an overweight young primi-gravida presented with a large pseudocyst of the spleen at third trimester. This cyst possibly developed due to a trivial rupture of spleen, but bleeding stopped spontaneously resulting in a pseudocyst. Her splenectomy was done 2 months after delivery. She recovered uneventfully.